Low Class Ib (HLA-G/Qa-2) MHC Protein Expression against Hsp-70 and VCAM-1 Profile on Preeclampsia. An observation on experimental animal Mus Musculus with Endothelial Dysfunction model - Sri Sulistyowati (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To analyze the expression of MHC class Ib Qa-2 protein (homologue to HLA-G in human), Hsp-70, and VCAM-1 in trophoblast cells of preeclampsia and control using endothelial dysfunction model on Mus Musculus. Method: Design of study is experimental study. Pregnant mice was treated with anti-Qa-2. Hsp-70 and VCAM-1 expressions of trophoblast cells was assessed on week I, II, and III. Result: Negative Qa-2 expression was achieved after administration of 40ng anti Qa-2 on the fifth day of pregnancy. The Hsp-70 and VCAM-1 expressions in negative Qa-2 mice (preeclampsia) was higher compared with those of positive Qa-2 mice (normal pregnancy) on week I, II and III. Conclusion: Low Qa-2 and high of HSP-70 and VCAM-1 expression might be useful for prediction of preeclampsia or endothelial dysfunction. [Indones J Obstet Gynecol 2010; 34-3: 103-7] Keywords: preeclampsia, HLA-G/Qa-2, Hsp-70, VCAM-1, endothelial dysfunction